Omega-3 fatty acids promote fatty acid utilization and production of pro-resolving lipid mediators in alternatively activated adipose tissue macrophages - Rombaldova, Martina; Janovska, Petra; Kopecky, Jan; Kuda, Ondrej (Biochemical and biophysical research communications, 2017)
It is becoming increasingly apparent that mutual interactions between adipocytes and immune cells are key to the integrated control of adipose tissue inflammation and lipid metabolism in obesity, but little is known about the non-inflammatory functions of adipose tissue macrophages (ATMs) and how they might be impacted by neighboring adipocytes. In the current study we used metabolipidomic analysis to examine the adaptations to lipid overload of M1 or M2 polarized macrophages co-incubated with adipocytes and explored potential benefits of omega-3 polyunsaturated fatty acids (PUFA). Macrophages adjust their metabolism to process excess lipids and M2 macrophages in turn modulate lipolysis and fatty acids (FA) re-esterification of adipocytes. While M1 macrophages tend to store surplus FA as triacylglycerols and cholesteryl esters in lipid droplets, M2 macrophages channel FA toward re-esterification and β-oxidation. Dietary omega-3 PUFA enhance β-oxidation in both M1 and M2. Our data document that ATMs contribute to lipid trafficking in adipose tissue and that omega-3 PUFA could modulate FA metabolism of ATMs.
Keywords: Male; Adipose Tissue; Fatty Acids, Omega-3; Adipose tissue macrophages; Fatty acid re-esterification; omega-3 mastné kyseliny; Omega-3 PUFA; tukové buňky; makrofágy; Mice, Inbred C57BL; lipolýza; esterifikace; Animals; metabolismus lipidů; kultivované buňky; myši inbrední C57BL; Lipid Metabolism; mastné kyseliny; mužské pohlaví; Macrophages; Cells, Cultured; Lipid mediators; Adipocytes; Fatty Acids; zvířata; Lipolysis; tuková tkáň; Esterification